2021
DOI: 10.1002/ase.2080
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Visualization of Human Anatomy through Art Using Technical Drawing Exercises

Abstract: Spatial visualization, the ability to mentally rotate three-dimensional (3D) images, plays a significant role in anatomy education. This study examines the impact of technical drawing exercises on the improvement of spatial visualization and anatomy education in a Neuroscience course. First-year medical students (n = 84) were randomly allocated into a control group (n = 41) or art-training group (n = 43). Variables including self-reported artistic drawing ability, previous technical drawing experience, or prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Students’ survey responses were consistent with studies showing that integration of drawing with traditional learning techniques increases retention and understanding of information. 7 , 11 , 12 Although the online assessment was open book and was not an objective measurement of the effectiveness of the interactive session, students’ comments and survey responses showed that the session increased their ability to discuss pelvic pathology and surgical anatomy. Our session is also consistent with the idea that learner-centered approaches where instruction is responsive, problem oriented, and democratic in nature lead to increased knowledge retention.…”
Section: Discussionmentioning
confidence: 99%
“…Students’ survey responses were consistent with studies showing that integration of drawing with traditional learning techniques increases retention and understanding of information. 7 , 11 , 12 Although the online assessment was open book and was not an objective measurement of the effectiveness of the interactive session, students’ comments and survey responses showed that the session increased their ability to discuss pelvic pathology and surgical anatomy. Our session is also consistent with the idea that learner-centered approaches where instruction is responsive, problem oriented, and democratic in nature lead to increased knowledge retention.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies examining the possible impact of artistic ability on anatomy examination performance. One study found no correlation between self‐reported artistic ability and performance in neuroscience examinations (Na et al, 2021). A second study reported a positive association between a positive attitude to drawing and spatial visualization ability (Alias et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although one study of veterinary students of anatomy reported that students who reported visual arts as a hobby spontaneously used drawing when learning anatomy (Laakkonen, 2021). Others have reported lower MRT scores in students who self-identify as 'artistic' (Na et al, 2021). A positive association between attitude to drawing and sketching and spatial visualization ability was reported among architecture but not engineering students, perhaps reflecting a difference in emphasis in the curricula (Alias et al, 2002).…”
Section: Attitude To Drawingmentioning
confidence: 99%
See 1 more Smart Citation
“…As a trait that is specific to each individual (i.e., a presage factor), VA could theoretically influence SAL (i.e., the learning process) and, therefore, the quality of the learning outcomes (termed ‘product’). Further, research has shown that VA can be improved through spatial training activities (Langlois et al, 2020), drawing activities (Reid et al, 2018; Na et al, 2021; Ritchie et al, 2023), or from having visual guidance during mental rotation tasks (Roach et al, 2019). Therefore, it may be possible to target VA as one mechanism for increasing the depth of students' learning approaches and the quality of their learning outcomes.…”
Section: Introductionmentioning
confidence: 99%